Enhancing Access to Finance for Technology Entrepreneurs : Analysis of Highly Innovative, High Growth Start-Ups in Vietnam, Cambodia, and Nepal - World Bank Group (Washington, DC, 2014)
The first part of the study provides contextual background to the financing gaps and associated barriers, which restrict access to finance for HI start-ups. These barriers are driven by both supply and demand sides of the financing equation. Supply side barriers include: high transaction costs associated with financing; high levels of credit risk associated with HI start-ups; high collateral required by financial institutions; non-conducive legal and regulatory environments for investment in HI start-ups; lack of start-up expertise and dedicated resources by financiers; and finance products that are not tailored to HI start-ups needs and circumstances. Demand side barriers include: reliance by HI start-ups on informal financing sources; lack of awareness on the process to apply for funding from formal financing sources; low levels of financial literacy by HI start-ups; and the fear of losing control by involving external investors. This section also contains a broad overview of the country frameworks governing the start-up sector, together with some of the initiatives relating to access to finance. The second part of the study covers the fieldwork undertaken in Vietnam, Cambodia, and Nepal. The fieldwork gathered views from investee firms (irrespective of whether they were successful in raising finance or not), investors, and other stakeholders. The fieldwork was aimed at understanding the severity of the financing gap for HI start-ups, the stage(s) of financing impacted by lack of access to finance, and the sources of financing for HI start-ups. Lastly, financing catalyst recommendations address non-financing impediments, which if overcome will have a positive impact on access to finance.